Application of an innovative grid-based surveillance strategy to ensure elimination and prevent reintroduction of malaria in high-risk border communities in China - Shen-ning Lu; Wei Ding; Jia-zhi Wang; Shou-qin Yin; Sheng-guo Li; Xing-wu Zhou; Qiu-li Xu; Xiao-dong Sun; Chris Cotter; Michelle S Hsiang; Allison Tatarsky; Roly Gosling; et al. (BMC, 2022)
Abstract Grid management is a grassroots governance strategy widely implemented in China since 2004 to improve the government's efficiency to actively find and solve problems among populated regions. A grid-based strategy surveillancing high-risk groups, including mobile and migrant populations (MMPs), in the China-Myanmar border region has played an indispensable role in promoting and consolidating the malaria elimination efforts by tracking and timely identification of potential importation or re-establishment of malaria among MMPs. A sequential mixed methods was implementated to explore the operational mechanism and best practices of the grid-based strategy including through the focus group discussions (FGDs), comparison of before and after the implementation of a grid-based strategy in the field sites, and data collection from the local health system.This paper distills the implementation mechanism and highlights the role of the grid-based strategy in the elimination and prevention of re-establishment of malaria transmission.